Gas barrier film
Patent Information
- Application Number
- JP2023128043
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-17
- Estimated Expiration
- 2043-08-04
AI Technical Summary
【0020】 本発明によれば、優れたガスバリア性を示すガスバリアフィルムを提供することができる。
Smart Images

Figure 2025023692000001 
Figure 2025023692000002 
Figure 2025023692000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a gas barrier film. More specifically, the present invention relates to a gas barrier film that exhibits excellent gas barrier properties. [Background technology]
[0002] Conventionally, gas barrier films using a plastic film or the like as a substrate have been used as packaging materials for food, medical products, etc., and as electronic device components for display devices, solar cells, etc. The gas barrier film has a gas barrier layer made of a metal or metal oxide formed thereon to block gases such as oxygen and water vapor.
[0003] Patent Document 1 discloses a gas barrier film having a gas barrier layer that contains silicon and oxygen and has a predetermined hardness. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-143551 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the gas barrier film described in Patent Document 1 leaves room for improvement.
[0006] The present invention has been made in view of the above-mentioned conventional inventions, and has an object to provide a gas barrier film that exhibits excellent gas barrier properties. [Means for solving the problem]
[0007] As a result of intensive research, the present inventors have focused on the relationship between the hardness and surface roughness of the gas barrier layer, and have found that by optimizing these properties, better gas barrier properties can be obtained, thereby completing the present invention. That is, the gas barrier film of the present invention that solves the above-mentioned problems mainly includes the following configurations.
[0008] (1) A gas barrier film comprising a substrate, a hard coat layer, and an inorganic oxide layer in this order, the inorganic oxide layer containing silicon oxide, and a ratio (H / Ra) of an indentation hardness H measured from a surface of the inorganic oxide layer by a nanoindentation method to a surface roughness Ra of the hard coat layer is 0.7 or more.
[0009] With this configuration, the gas barrier film exhibits excellent gas barrier properties.
[0010] (2) A gas barrier film comprising a substrate, a hard coat layer, and an inorganic oxide layer in this order, the inorganic oxide layer containing silicon oxide, and a ratio (E / Ra) of an indentation modulus E measured from a surface of the inorganic oxide layer by a nanoindentation method to a surface roughness Ra of the hard coat layer of 3.4 or more.
[0011] With this configuration, the gas barrier film exhibits excellent gas barrier properties.
[0012] (3) A gas barrier film comprising a substrate, a hard coat layer, and an inorganic oxide layer in this order, the inorganic oxide layer containing silicon oxide, the indentation hardness measured from the surface of the inorganic oxide layer by a nanoindentation method being 0.55 GPa or more, the indentation elastic modulus being 5.30 GPa or more, and the surface roughness Ra of the hard coat layer being 2.3 nm or less.
[0013] With this configuration, the gas barrier film exhibits excellent gas barrier properties.
[0014] (4) The gas barrier film according to any one of (1) to (3), further comprising a transparent conductive layer on the surface of the inorganic oxide layer opposite to the hard coat layer, the transparent conductive layer containing indium tin oxide.
[0015] With this configuration, the gas barrier film exhibits excellent gas barrier properties and electrical conductivity.
[0016] (5) The gas barrier film according to (4), wherein the indentation hardness of the transparent conductive layer measured from the surface thereof by a nanoindentation method is 0.80 GPa or more.
[0017] With this configuration, the gas barrier film exhibits excellent gas barrier properties and electrical conductivity.
[0018] (6) The gas barrier film according to any one of (1) to (3), further comprising a transparent conductive layer on the surface of the substrate opposite to the hard coat layer, the transparent conductive layer containing indium tin oxide.
[0019] With this configuration, the gas barrier film exhibits excellent gas barrier properties and electrical conductivity. Effect of the Invention
[0020] According to the present invention, a gas barrier film exhibiting excellent gas barrier properties can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] <Gas barrier film> (First embodiment) The gas barrier film according to one embodiment of the present invention includes a substrate, a hard coat layer, and an inorganic oxide layer in this order. The inorganic oxide layer contains silicon oxide. The ratio (H / Ra) of the indentation hardness H measured from the surface of the inorganic oxide layer by a nanoindentation method to the surface roughness Ra of the hard coat layer is 0.7 or more. Each of the configurations will be described below.
[0022] (base material) The substrate may be a resin film commonly used in gas barrier films. For example, the substrate may be a plastic film or a plastic sheet such as polyethylene terephthalate (PET), cycloolefin polymer (COP), polyethylene (PE), polyimide (PI), polyethylene naphthalate (PEN), polycarbonate (PC), or triacetyl cellulose (TAC). In addition, the substrate may be a flame-retardant substrate obtained by imparting flame retardancy to polyethylene terephthalate (PET), polyethylene naphthalate (PEN), or polycarbonate (PC). Among these, the substrate is preferably made of a material having flexibility (pliability) such as a plastic film. This allows the gas barrier film to be suitably used in a wide range of applications, such as electronic device parts such as displays and solar cell panels.
[0023] The thickness of the substrate is not particularly limited. For example, the thickness of the substrate is preferably 12 μm or more, more preferably 25 μm or more. The thickness of the substrate is preferably 200 μm or less, more preferably 125 μm or less. When the thickness of the substrate is within the above range, the obtained gas barrier film can exhibit appropriate rigidity and strength.
[0024] (Hard coat layer) The hard coat layer is provided on the substrate. The resin material constituting the hard coat layer is not particularly limited. For example, the resin material constituting the hard coat layer is a thermosetting resin made of a polyester resin, an acrylic resin, a polyurethane resin, or an epoxy resin, and a photocurable resin (acrylic resin, epoxy resin), etc. Among these, the resin material constituting the hard coat layer is preferably a photocurable resin, more preferably a urethane acrylate, in that it has a short curing time and exhibits excellent hard coat properties.
[0025] The method for forming the hard coat layer is not particularly limited. For example, the hard coat layer can be formed on the substrate by gravure coating, reverse coating, nano coating, bar coating, die coating, dipping, screen printing, or the like.
[0026] The thickness of the hard coat layer is not particularly limited. The thickness of the hard coat layer is preferably 0.5 μm or more, more preferably 1.0 μm or more. Also, the thickness of the hard coat layer is preferably 20 μm or less, more preferably 10 μm or less. When the thickness of the hard coat layer is within the above range, the gas barrier film is likely to be imparted with sufficient surface hardness.
[0027] (Inorganic oxide layer) The inorganic oxide layer is a layer containing silicon oxide provided on the hard coat layer.
[0028] The silicon oxide is a silicon oxide represented by the compositional formula SiOx (0 < x ≤ 2, preferably 1 ≤ x < 2). The x in SiOx may be an inclined film with an inclination in the thickness direction of the inorganic oxide layer or a uniform film.
[0029] The content of the silicon oxide is preferably 95% by mass or more, more preferably 98% by mass or more, and even more preferably 99% by mass or more in the compounds constituting the inorganic oxide layer. In this embodiment, the inorganic oxide layer may contain impurities that are inevitably contained. When the content of the silicon oxide is within the above range, the gas barrier film can exhibit excellent gas barrier properties.
[0030] The thickness of the inorganic oxide layer is not particularly limited. For example, the thickness of the inorganic oxide layer is preferably 20 nm or more, more preferably 100 nm or more. The thickness of the inorganic oxide layer is preferably 1000 nm or less, more preferably 500 nm or less. When the thickness of the inorganic oxide layer is within the above range, the resulting gas barrier film exhibits excellent gas barrier properties.
[0031] The method of forming the inorganic oxide layer is not particularly limited. For example, the inorganic oxide layer may be formed by a sputtering method, a wet coating method, or a combination of a sputtering method and a wet coating method. In the case of forming by a sputtering method, specifically, the inorganic oxide layer may be formed on the substrate by a reactive sputtering method in a mixed gas atmosphere of argon and oxygen using a target made of silicon. In the case of forming by a wet coating method, specifically, the inorganic oxide layer may be formed by applying polysilazane (PHPS) to the substrate by a known wet coating method and converting it into silicon oxide.
[0032] The ratio (H / Ra) of the indentation hardness H measured from the surface of the inorganic oxide layer by the nanoindentation method to the surface roughness Ra of the hard coat layer is 0.7 or more, preferably 0.8 or more, more preferably 1.0 or more, and even more preferably 2.0 or more. The ratio (H / Ra) is preferably 4.0 or less, more preferably 3.7 or less. If the ratio (H / Ra) is less than 0.7, the gas barrier film has poor gas barrier properties. In this specification, when discussing the value of the ratio (H / Ra), the value calculated with the unit of H being GPa and the unit of Ra being nm is used. The "nanoindentation method" is a method in which a special diamond indenter is pressed into the surface of a sample to measure the load (indentation strength) and displacement (indentation depth). The indentation hardness H can be measured using a nanoindentation tester (ENT-2100, manufactured by Elionix Co., Ltd.) with a test load of 0.1 mN and an indentation depth of 10% or less of the film thickness of the outermost layer of the layer to be measured. The surface roughness Ra can be measured using a white light interference microscope (NT-9100, manufactured by Veeco Co., Ltd.) with a 5x objective lens in Phase-Shift Interferometry mode.
[0033] (Transparent conductive layer) The transparent conductive layer can be suitably formed on the surface of the inorganic oxide layer opposite to the hard coat layer. The transparent conductive layer can also be suitably formed on the surface of the substrate opposite to the hard coat layer. The material contained in the transparent conductive layer is not particularly limited as long as it is a transparent conductive material that exhibits transparency and conductivity. An example is a metal oxide of a metal such as indium, tin, zinc, gallium, antimony, titanium, silicon, zirconium, magnesium, aluminum, gold, silver, copper, palladium, or tungsten. Among these, the transparent conductive layer preferably contains indium tin oxide (ITO), aluminum oxide, indium zinc oxide (IZO), aluminum-added zinc oxide (AZO), gallium-added zinc oxide (GZO), indium cerium oxide (ICO), or the like, and particularly preferably contains ITO. The transparent conductive material contained in the transparent conductive layer may be one of these materials, or may be a plurality of materials. The transparent conductive material contained in the transparent conductive layer is preferably 95% by mass or more, more preferably 98% by mass or more, and even more preferably 99% by mass or more, of the compounds constituting the transparent conductive layer. In this embodiment, the transparent conductive layer may contain impurities that are inevitably contained. By providing such a transparent conductive layer, the gas barrier film has excellent gas barrier properties and conductivity.
[0034] The thickness of the transparent conductive layer is not particularly limited. For example, the thickness of the transparent conductive layer is preferably 13 nm or more, more preferably 15 nm or more. The thickness of the transparent conductive layer is preferably 500 nm or less, more preferably 300 nm or less. When the thickness of the transparent conductive layer is within the above range, the gas barrier film can obtain excellent conductivity and transparency.
[0035] The indentation hardness measured from the surface of the transparent conductive layer by nanoindentation is preferably 0.80 GPa or more, more preferably 1.00 GPa or more, even more preferably 2.00 GPa or more, and particularly preferably 2.60 GPa or more. This makes the gas barrier film more excellent in gas barrier properties. The indentation hardness can be measured using a nanoindentation tester (ENT-2100, manufactured by Elionix Co., Ltd.) under the conditions of a test load of 0.1 mN and an indentation depth of 10% or less of the film thickness of the outermost layer of the layer to be measured.
[0036] The method of forming the transparent conductive layer is not particularly limited. For example, the transparent conductive layer can be formed on the inorganic oxide layer or the substrate by a dry coating method such as a vacuum deposition method, a sputtering method, or an ion plating method, or a wet coating method (coating method), etc., using a composition constituting the transparent conductive layer. Among these, the transparent conductive layer is preferably formed by a dry coating method because it is easy to form a thin film, and is preferably formed by reactive sputtering using a metal oxide target (ITO) by a magnetron sputtering method. At this time, for example, oxygen, nitrogen, water vapor, etc. may be introduced, or means such as ozone addition, plasma irradiation, and ion assist may be used in combination.
[0037] As described above, according to this embodiment, the gas barrier film exhibits excellent gas barrier properties.
[0038] Second Embodiment The gas barrier film according to one embodiment of the present invention comprises a substrate, a hard coat layer, and an inorganic oxide layer in this order. The inorganic oxide layer contains silicon oxide. The ratio (E / Ra) of the indentation modulus E measured from the surface of the inorganic oxide layer by a nanoindentation method to the surface roughness Ra of the hard coat layer is 3.4 or more. Each of the configurations will be described below. In the following description, each layer is the same as that described above in the first embodiment, and therefore the description will be omitted as appropriate.
[0039] In the gas barrier film of this embodiment, the ratio (E / Ra) of the indentation modulus E measured from the surface of the inorganic oxide layer by nanoindentation to the surface roughness Ra of the hard coat layer may be 3.4 or more, preferably 4.5 or more, more preferably 5.8 or more, and even more preferably 8.3 or more. The ratio (E / Ra) is preferably 20.0 or less, more preferably 19.0 or less. If the ratio (E / Ra) is less than 3.4, the gas barrier film has poor gas barrier properties. In addition, when discussing the value of the ratio (E / Ra) in this specification, the value calculated with the unit of E being GPa and the unit of Ra being nm is used. The indentation modulus E can be measured using a nanoindentation tester (ENT-2100, manufactured by Elionix Co., Ltd.) under the conditions of a test load of 0.1 mN and an indentation depth of 10% or less of the film thickness of the outermost layer of the layer to be measured.
[0040] The gas barrier film of this embodiment may be provided with a transparent conductive layer similar to that of the gas barrier film described above in the first embodiment.
[0041] As described above, the gas barrier film of the present embodiment exhibits excellent gas barrier properties.
[0042] (Third embodiment) The gas barrier film of one embodiment of the present invention comprises a substrate, a hard coat layer, and an inorganic oxide layer in this order. The inorganic oxide layer contains silicon oxide. The indentation hardness measured from the surface of the inorganic oxide layer by nanoindentation is 0.55 GPa or more, and the indentation elastic modulus is 5.30 GPa or more. The surface roughness Ra of the hard coat layer is 2.3 nm or less. Each configuration will be described below. In the following description, each layer is the same as that described above in the first embodiment, so the description will be omitted as appropriate.
[0043] In the gas barrier film of this embodiment, the indentation hardness measured from the surface of the inorganic oxide layer by the nanoindentation method may be 0.55 GPa or more, preferably 0.79 GPa or more, more preferably 1.37 GPa or more, and even more preferably 1.90 GPa or more. The indentation hardness is preferably 3.00 GPa or less, more preferably 2.60 GPa or less. If the indentation hardness is less than 0.55 GPa, the gas barrier film has poor gas barrier properties. The indentation hardness can be measured using a nanoindentation tester (ENT-2100, manufactured by Elionix Co., Ltd.) under the conditions of a test load of 0.1 mN and an indentation depth of 10% or less of the film thickness of the outermost layer of the layer to be measured.
[0044] In the gas barrier film of this embodiment, the indentation modulus measured from the surface of the inorganic oxide layer by nanoindentation method may be 5.30 GPa or more, preferably 5.80 GPa or more, more preferably 7.80 GPa or more, and even more preferably 10.20 GPa or more. In addition, the indentation modulus is preferably 15.00 GPa or less, more preferably 13.00 GPa or less. When the indentation modulus is within the above range, the gas barrier film has excellent gas barrier properties. The indentation modulus can be measured using a nanoindentation tester (ENT-2100, manufactured by Elionix Co., Ltd.) under the conditions of a test load of 0.1 mN and an indentation depth of 10% or less of the film thickness of the outermost layer of the layer to be measured.
[0045] In the gas barrier film of this embodiment, the surface roughness Ra of the hard coat layer may be 2.3 nm or less, preferably 2.0 nm or less, and more preferably 1.4 nm or less. The surface roughness Ra is preferably 0.1 nm or more, and more preferably 0.5 nm or more. If the surface roughness is more than 2.3 nm, the gas barrier film has poor gas barrier properties. The surface roughness Ra can be measured using a white light interference microscope (NT-9100, manufactured by Veeco) with a 5x objective lens in Phase-Shift Interferometry mode.
[0046] The gas barrier film of this embodiment may be provided with a transparent conductive layer similar to that of the gas barrier film described above in the first embodiment.
[0047] As described above, the gas barrier film of the present embodiment exhibits excellent gas barrier properties. EXAMPLES
[0048] The present invention will be described in more detail below with reference to examples. The present invention is not limited to these examples. In addition, unless otherwise specified, "%" means "% by mass".
[0049] Example 1 A PET film (thickness: 50 μm) was used as the substrate, and a hard coat layer (HC) made of coating material 1 (UV-1700B, manufactured by Mitsubishi Chemical Corporation) was applied onto the substrate using a bar coater, dried at 80 °C for 1 minute, and then coated with 300 mJ / cm under a nitrogen atmosphere. 2 The resulting hard coat layer had a thickness of 1.5 μm. Next, an inorganic oxide layer (thickness 25 nm) of SiOx was formed on the hard coat layer by reactive sputtering using a magnetron sputtering method with a Si target, to obtain a gas barrier film.
[0050] Example 2 A PET film (thickness: 50 μm) was used as the substrate, and a hard coat layer (HC) made of coating material 2 (Z-773-ML, manufactured by Aica Kogyo Co., Ltd.) was applied onto the substrate using a bar coater, dried at 80 °C for 1 minute, and then applied with 300 mJ / cm under a nitrogen atmosphere. 2 The resulting hard coat layer had a thickness of 1.5 μm. Next, an inorganic oxide layer was formed on the hard coat layer by the following method. First, PHPS (polysilazane) was applied onto the hard coat layer by a wet process (bar coater), dried at 140° C. for 1 minute, and left to stand for 2 weeks under 25° C. conditions to form a silicon oxide. The resulting SiOx (PHPS conversion layer) had a thickness of 160 nm. Next, SiOx was formed to a thickness of 25 nm on the SiOx (PHPS conversion layer) by reactive sputtering using a magnetron sputtering method using a Si target, to obtain a gas barrier film.
[0051] Example 3 A gas barrier film was produced in the same manner as in Example 2, except that the coating material for the hard coat layer was changed to Coating Material 1 (UV-1700B, manufactured by Mitsubishi Chemical Corporation).
[0052] Example 4 A gas barrier film was produced in the same manner as in Example 2, except that the coating material for the hard coat layer was changed to Coating Material 3 (UV-7630B, manufactured by Mitsubishi Chemical Corporation).
[0053] Example 5 A gas barrier film was produced in the same manner as in Example 2, except that the coating material for the hard coat layer was changed to Coating Material 4 (A-DCP, manufactured by Shin-Nakamura Chemical Co., Ltd.).
[0054] Example 6 A gas barrier film was produced in the same manner as in Example 2, except that the coating material for the hard coat layer was changed to Coating Material 5 (A-DPH, manufactured by Shin-Nakamura Chemical Co., Ltd.).
[0055] Comparative Example 1 A gas barrier film was produced in the same manner as in Example 1, except that the coating material for the hard coat layer was changed to Coating Material 6 (UV-7610B, manufactured by Mitsubishi Chemical Corporation).
[0056] Comparative Example 2 A gas barrier film was produced in the same manner as in Example 2, except that the coating material for the hard coat layer was changed to Coating Material 6 (UV-7610B, manufactured by Mitsubishi Chemical Corporation).
[0057] Comparative Example 3 A gas barrier film was produced in the same manner as in Example 1, except that the coating material for the hard coat layer was changed to Coating Material 2 (Z-773-ML, manufactured by Aica Kogyo Co., Ltd.).
[0058] Comparative Example 4 A gas barrier film was produced in the same manner as in Example 1, except that the coating material for the hard coat layer was changed to Coating Material 3 (UV-7630B, manufactured by Mitsubishi Chemical Corporation).
[0059] Comparative Example 5 A gas barrier film was produced in the same manner as in Example 1, except that the coating material for the hard coat layer was changed to Coating Material 4 (A-DCP, manufactured by Shin-Nakamura Chemical Co., Ltd.).
[0060] Example 7 A transparent conductive layer was formed by reactive sputtering by magnetron sputtering using an ITO target (SnO2: 10 mass%) on the inorganic oxide layer of the gas barrier film produced in Example 1. The thickness of the ITO transparent conductive layer was 18 nm.
[0061] (Examples 8 to 12, Comparative Examples 6 to 10) A transparent conductive layer was formed in the same manner as in Example 7 on the inorganic oxide layer of the gas barrier film produced in Example 8, Example 9, Example 3, Example 10, Example 4, Example 11, Example 5, Example 12, Example 6, Comparative Example 6, Comparative Example 1, Comparative Example 7, Comparative Example 2, Comparative Example 8, Comparative Example 3, Comparative Example 9, Comparative Example 4, and Comparative Example 10, Comparative Example 5.
[0062] [Table 1]
[0063] [Table 2]
[0064] The adhesion (cross-cut peel test), surface roughness, indentation hardness, indentation elastic modulus, thermal expansion coefficient, and water vapor transmission rate (WVTR) were measured by the following evaluation methods. The results are shown in Tables 1 to 3.
[0065] <Adhesion (checkerboard peel test)> The test surface was cut into 11 equal intervals (1.5 mm), turned 90 degrees, and cut into 11 more equal intervals (1.5 mm) to create 100 squares cut into a 10 x 10 grid pattern. Cellophane tape (manufactured by Nichiban Co., Ltd., product number: CT405AP-18) was attached on top of the test surface and allowed to stand for 1 minute. The tape was then held at the end and instantly peeled off in a direction perpendicular to the pasted surface, and the number of squares remaining without peeling was counted. <Surface roughness> The surface roughness (Ra, Rz, Rt) was measured using a white light interference microscope (NT-9100, Veeco) with a 5x objective lens in Phase-Shift Interferometry mode. <Indentation hardness> A nanoindentation tester (ENT-2100, manufactured by Elionix Co., Ltd.) was used to perform the measurement under the condition of a test load of 0.1 mN. The indentation depth was set to 2.5 nm or less when measuring from the surface of the inorganic oxide layer, and 1.8 nm or less when measuring from the surface of the transparent conductive layer. <Indentation elastic modulus> A nanoindentation tester (ENT-2100, manufactured by Elionix Co., Ltd.) was used to perform the measurement under the condition of a test load of 0.1 mN. The indentation depth was set to 2.5 nm or less when measuring from the surface of the inorganic oxide layer, and 1.8 nm or less when measuring from the surface of the transparent conductive layer. <Thermal expansion coefficient> The measurement sample (70 mm square) was sandwiched between transparent glass plates, and the dimensions of the measurement sample were measured at each temperature. The measurement of the dimensions of the measurement sample was performed using an image dimensioner (IM6010, Keyence Corporation). <Water vapor transmission rate (WVTR)> The water vapor transmission rate (%) was measured using DELTAPERM (DP-UH2AT, Technolox) in accordance with the "differential pressure method (ISO 15106-5)".
[0066] [Table 3]
[0067] As shown in Tables 1 to 3, the gas barrier film of the present invention had a small water vapor permeability and excellent gas barrier properties.
Claims
1. A substrate, a hard coat layer, and an inorganic oxide layer are provided in this order, The inorganic oxide layer includes a silicon oxide, A gas barrier film, wherein a ratio (H / Ra) of an indentation hardness H measured from the surface of the inorganic oxide layer by a nanoindentation method to a surface roughness Ra of the hard coat layer is 0.7 or more.
2. A substrate, a hard coat layer, and an inorganic oxide layer are provided in this order, The inorganic oxide layer includes a silicon oxide, A gas barrier film, wherein a ratio (E / Ra) of an indentation modulus E measured from the surface of the inorganic oxide layer by a nanoindentation method to a surface roughness Ra of the hard coat layer is 3.4 or more.
3. A substrate, a hard coat layer, and an inorganic oxide layer are provided in this order, The inorganic oxide layer includes a silicon oxide, the indentation hardness measured from the surface of the inorganic oxide layer by a nanoindentation method is 0.55 GPa or more, and the indentation elastic modulus is 5.30 GPa or more; The gas barrier film, wherein the hard coat layer has a surface roughness Ra of 2.3 nm or less.
4. a transparent conductive layer is provided on the surface of the inorganic oxide layer opposite to the hard coat layer; The gas barrier film according to any one of claims 1 to 3, wherein the transparent conductive layer contains indium tin oxide.
5. 5. The gas barrier film according to claim 4, wherein an indentation hardness of the transparent conductive layer measured from the surface by a nanoindentation method is 0.80 GPa or more.
6. a transparent conductive layer is provided on the surface of the substrate opposite to the hard coat layer; The gas barrier film according to any one of claims 1 to 3, wherein the transparent conductive layer contains indium tin oxide.
Citation Information
Patent Citations
Reflection preventing film and method for manufacturing the same, and reflection preventing layer-attached polarization plate
JP2017227898A
Transparent conductive film and transparent conductive film laminate
JP2019079637A
Gas barrier film
JP2019089269A
Transparent conductive film with protective film
JP2020161483A
Gas barrier film
JP2021123068A